The Influence Of Online Media Advertising And Product Quality On Honda Mobilio Buying Interest Through Brand Awareness - Ikin Sodikin; wachjuni wachjuni (Universitas Kuningan, 2020)
ABSTRACTThis study aims to determine the direct and indirect effects of video advertising through online media and product quality on buying interest with brand awareness as an intervening variable. The sample in this study was people in the three regions of Cirebon with the category of having seen video advertisements on online media, having driven or bought a Honda Mobilio product and were over 20 years old with samples taken as many as 100 people. This research instrument in the form of a questionnaire by distributing through the help of Google forms. The data analysis technique used is Structural Equation Modeling (SEM). The test results of the proposed hypothesis show that (1) video advertising through online media has no effect on brand awareness and is significant. (2) video advertisements through online media have no effect on buying interest and are not significant. (3) product quality influences brand awareness and is significant. (4) product quality has no effect on buying interest and is not significant. (5) brand awareness has no influence on buying interest and is significant. (6) Variable video advertisements through online media and product quality together affect brand awareness. (7) video advertising through online media, product quality and brand awareness together influence buying interest. (8) video advertising through online media has no effect on buying interest through brand awareness. (9) product quality influences buying interest through brand awareness.Keywords: Video Advertising Through Online Media, Product Quality, Buy Brand Awareness